Pengaruh Pertumbuhan Ekonomi, Kurs Rupiah, Inflasi Dan Harga Emas Dunia Terhadap Indeks Harga Saham Jakarta Islamic Index Periode 2014-2023 - M Fadli Sukma Nasution; Nurjanah; Chahayu Astina (FEBI IAIN Langsa, 2025)
This study aims to analyze the influence of macroeconomic variables on the Jakarta Islamic Index (JII) stock price index during the 2014-2023 period. The independent variables examined include economic growth, exchange rates, inflation, and global gold prices. This research utilizes quarterly data analyzed through multiple linear regression using EViews 12 software. The results of the study reveal that, partially, exchange rates and global gold prices significantly influence the JII stock price index. Conversely, economic growth and inflation do not significantly affect the JII stock price index. Simultaneously, the four variables collectively have a significant influence on the JII stock price index. The Adjusted R-squared value indicates that the independent variables in this study explain 53.01% of the variation in the JII stock price index, while the remaining 46.99% is influenced by other factors not included in this study.